Exploring patterns and predictors of suicidal ideation among pregnant and postpartum women living with HIV in Kilimanjaro, Tanzania. (1st September 2020) - Knettel, Brandon A.; Mwamba, Rimel N.; Minja, Linda; Goldston, David B.; Boshe, Judith; Watt, Melissa H.
Abstract : Objective: Pregnant and postpartum women living with HIV face disproportionate risk of depression and suicide, particularly in low-income and middle-income countries. This study examined patterns and predictors of suicidal ideation among women living with HIV in antenatal care in Kilimanjaro, Tanzania. Design: We conducted a longitudinal cohort study of 200 pregnant women living with HIV, with surveys conducted during pregnancy and 6 months postpartum. Methods: Pregnant women were recruited during HIV and antenatal care visits at nine clinics. A structured questionnaire was verbally administered in Kiswahili by a trained study nurse. We used simple frequencies and t -tests to measure patterns of suicidal ideation and logistic regression to assess factors associated with suicidal ideation. Results: Suicidal ideation was endorsed by 12.8% of women during pregnancy and decreased significantly to 3.9% by 6 months postpartum. Ideation was not significantly greater among participants newly diagnosed with HIV. In univariable analyses, suicidal ideation was associated with depression, anxiety, HIV stigma, single relationship status, unknown HIV status of the father of the baby, negative attitudes about antiretroviral medication, and low social support. In the multivariable model, women experiencing anxiety and HIV stigma were significantly more likely to endorse suicidal ideation during pregnancy. Conclusion: Suicidal ideation and associated feelings of hopelessness are a critical challenge in antenatal care among women living with HIV, with important implications for quality of life, care engagement, and survival. To better support patients, targeted approaches to address anxiety, depression, stigma, and hopelessness must be prioritized, including crisis support for suicide prevention.